THE CONSTITUTIONAL COURT’S DECISION ON THE AMENDMENT OF LAW NO. 1/1974 ON MARRIAGE - Muhibbin, Moch.; Triadi, Dr. Irwan (jfpublisher, 2023)
This research was conducted to determine the impact of Constitutional Court Decision No. 46/PUU-VIII/2010 related to the position of children out of wedlock and Constitutional Court Decision No. 69/PUU-XIII/2015 on marriage agreements on the amendment of Law No. 1/1974 on marriage. This research used juridical normative methods with a statutory approach. In addition, the data analysis used is descriptive qualitative. The results of the research indicate that there are three decisions of the Constitutional Court with the verdict “granted”, including the following Constitutional Court Decision Number 46/PUU-VIII/2010; Constitutional Court Decision Number 69/PUU-XIII/2015; and Constitutional Court Decision Number 22/PUU-XV/2017 regarding the age limit of marriage. Constitutional Court Decision Number 22/PUU-XV/2017 has been followed up with the amendment of Law No. 16/2019 concerning Amendments to Law No.1/1974 on Marriage. However, Constitutional Court Decision Number 46/PUU-VIII/2010 and Constitutional Court Decision Number 69/PUU-XIII/2015 were omitted in the Law No. 16/2019 amendment. Therefore, the law-forming apparatus needs to implement the legislative review and executive review mechanisms that can be used as an effort to amend a statutory regulation through the legislative and executive institutions, in this case, Constitutional Court Decision Number 46/PUU-VIII/2010 and Constitutional Court Decision Number 69/PUU-XIII/2015. In addition, it is also essential to strengthen the system for monitoring the follow-up of Constitutional Court decisions that are final and binding.